Catalytic Hydrolysis of Ethyl Acetate using Cation Exchange Resin (Amberlyst - 15) : A Kinetic Study - K. R. Ayyappan; Amrit Pal Toor; Ri Gupta; Ajay Bansal; R. K. Wanchoo (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2009)
The kinetic behavior of the heterogeneous hydrolysis of aqueous ethyl acetate over an acidic cation exchange resin, Amberlyst 15, was investigated. The experiments were carried out in a fixed bed reactor at temperatures from 313.15 to 343.15 K and feed molar ratios ,θBo (water to ethyl acetate) from 62.4 to 265.88. The conversion of ethyl acetate was found to increase with increasing reaction temperature. Gas bubble formation was observed at reaction temperature ≥ 343.15K. Absence of mass transfer resistance was verified by conducting the experiments at different catalyst loadings (20 g, 40 g, 64 g) under varied feed flow rates (1 to 25 cm3/min ). The kinetic data was correlated with pseudo first order model and model parameters were determined using Nelder-Mead algorithm for minimizing the objective function. © 2009 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)